Hospital-Level Variations in Rates of Inpatient Urinary Tract Infections in Stroke - Tørnes, Michelle; McLernon, David J.; Bachmann, Max O.; Musgrave, Stanley D.; Warburton, Elizabeth A.; Potter, John F.; Myint, Phyo Kyaw (Frontiers in Neurology, 2019)
Background and purpose: Urinary tract infection (UTI) is one of the most common complications following stroke and has prognostic significance. UTI rates have been shown to vary between hospitals, but it is unclear whether this is due to case-mix differences or heterogeneities in care among hospitals. Methods: A prospective multi-center cohort study of acute stroke patients admitted to eight National Health Service acute hospital trusts within the Anglia Stroke & Heart Clinical Network between 2009 and 2011 was conducted. We modelled the association between hospital (as a fixed-effect) and inpatient UTI using a multivariable logistic regression model, adjusting for established patient-level risk factors. We graphically and descriptively analyzed heterogeneities in hospital-level characteristics. Results: We included 2241 stroke admissions in our analysis; 171 (7.6%) acquired UTI as an inpatient. UTI rates varied significantly between the eight hospitals, ranging from 3% to 11%. The hospital that had the lowest odds of UTI (odds ratio (OR)=0.50 (95% confidence interval (CI) 0.22 to 1.11)) in adjusted analysis, had the highest number of junior doctors and occupational therapists per five beds of all hospitals. The hospital with the highest adjusted UTI rate (OR=2.69 (1.56 to 4.64)) was tertiary, the largest and had the highest volume of stroke patients, lowest number of stroke unit beds per 100 admissions, and the highest number of hospital beds per CT scanner. Conclusions: There is hospital-level variation in post-stroke UTI. Our results suggest the potential influence of service characteristics independently of patient-level factors which may be amenable to address to improve the ultimate stroke outcome.